Germanistik : Internationales Referatenorgan mit bibliographischen Hinweisen (De Gruyter, 2002)
Germanistik is the central international journal covering the study of German language and literature. Each volume contains some 8,000 published titles in its bibliography. Selected titles are critically reviewed. More than 800 scholars, both German and international, co-operate with the editorial staff.